Influence of wet foam stability on the microstructure of ceramic shell foams - Naiane Paiva Stochero; Elisângela Guzi de Moraes; Antonio Pedro Novaes de Oliveira (Open Ceramics, 2020)
In this study, recycled ceramic shell particles from the mold used in precision casting, which consists of coating a wax model with several layers (shell) of mullite and zirconia particles of different sizes, were used as raw material to prepare stable wet-foams by direct foaming and gelcasting using ovalbumin. The control of suspension parameters, such as pH, dispersant concentration, solids concentration and stirring velocity, can influence the foam stability against destabilization mechanisms (such as drainage, coalescence, and Ostwald ripening), optimizing the final properties of the cellular ceramic structures. The rheological behavior of suspensions and the gel point temperature of foams was also evaluated. The evolution of the bubbles-sizes (as a function of time) into the wet foam structure was analyzed by Axio Vision LE and ImageJ software. The fired ceramic shell foam (1550 ​°C, 2 ​°C/min, for 2 ​h) exhibited porosities higher than 80%, characterized by a highly interconnected network of spherical pores, with sizes ranging from 518 ​± ​29 to 1088 ​± ​103 ​μm and compressive strength of 0.9 ​± ​0.2 ​MPa. The morphological features and mechanical strength of the obtained foam indicating the possibility that it could be employed as low-cost replacement for radiant porous burners applications.